HYDROLOGICAL STUDIES IN THE INSHORE WATERS OF MANGALORE DURING 1964-1973 - Radhakrishnan, N S (Indian Journal of Fisheries, 2011)
Observations on the hydrological conditions over a decade of the inshorewaters of Mangalore are presented and discussed, with an emphasis on the effectsof the southwest monsoon in modifying the hydrographic characteristics. The annualvariation of temperature was bimodal with peaks occurring prior to the two monsoonperiods, and the minimum occurring during the monsoons. The salinity andpH indicated a sharp fall during the southwest monsoon period, and the phosphateand silicate contents exhibited a remarkable increase during the same period.The dissolved oxygen contents also showed a decline during the southwest monsoonperiod.